Fire Simulation and Cardiovascular Health in Firefighters. Issue 14 (4th April 2017) - Hunter, Amanda L.; Shah, Anoop S.V.; Langrish, Jeremy P.; Raftis, Jennifer B.; Lucking, Andrew J.; Brittan, Mairi; Venkatasubramanian, Sowmya; Stables, Catherine L.; Stelzle, Dominik; Marshall, James; Graveling, Richard; Flapan, Andrew D.; et al.
Abstract : Background: Rates of myocardial infarction in firefighters are increased during fire suppression duties, and are likely to reflect a combination of factors including extreme physical exertion and heat exposure. We assessed the effects of simulated fire suppression on measures of cardiovascular health in healthy firefighters. Methods: In an open-label randomized crossover study, 19 healthy firefighters (age, 41±7 years; 16 males) performed a standardized training exercise in a fire simulation facility or light duties for 20 minutes. After each exposure, ex vivo thrombus formation, fibrinolysis, platelet activation, and forearm blood flow in response to intra-arterial infusions of endothelial-dependent and -independent vasodilators were measured. Results: After fire simulation training, core temperature increased (1.0±0.1°C) and weight reduced (0.46±0.14 kg, P <0.001 for both). In comparison with control, exposure to fire simulation increased thrombus formation under low-shear (73±14%) and high-shear (66±14%) conditions ( P <0.001 for both) and increased platelet-monocyte binding (7±10%, P =0.03). There was a dose-dependent increase in forearm blood flow with all vasodilators ( P <0.001), which was attenuated by fire simulation in response to acetylcholine ( P =0.01) and sodium nitroprusside ( P =0.004). This was associated with a rise in fibrinolytic capacity, asymptomatic myocardial ischemia, and an increase in plasma cardiac troponin I concentrations (1.4 [0.8–2.5] versus 3.0 [1.7–6.4] ng/L, P =0.010). Conclusions: Exposure to extreme heat and physical exertion during fire suppression activates platelets, increases thrombus formation, impairs vascular function, and promotes myocardial ischemia and injury in healthy firefighters. Our findings provide pathogenic mechanisms to explain the association between fire suppression activity and acute myocardial infarction in firefighters. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01812317.